The Influence of Teacher Professionalism on Teacher Performance at Al-Ittihadiyah Integrated SMP Ciampea Udik Bogor - Syamsul Rizal Mz; Rahma Nurhadi Yantina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The quality of a school is determined by the quality of its teachers. The better the quality of a teacher the better the performance will be. Therefore, a teacher is required to master every competency that will support his work in educating the nation’s next generation. This study aims to find out if there is an influence between variable X, namely teacher professionalism on variable Y teacher performance. This research was conducted at SMP Terpadu Al-Ittihadiyah Ciampea Udik Bogor. The research method used is descriptive quantitative method. The number of respondents in this study as many as 10 people, namely all teachers at Integrated Junior High School Al-Ittihadiyah as the primary data source with the technique of spreading questionnaires and 1 principal as a secondary data source with interview techniques that are used as reinforcements in the results of this study. The tests in this study used validity, reliability tests using the Cronbach Alpha formula, normality tests, linearity tests and correlation coefficient tests. The data analysis in this study used a simple regression test or t test. The result of t test calculation from this study is with a sig value of 0.071 > 0.05 and t count of 2.081 < t table 2.303. This shows that there is no significant influence between teacher professionalism and teacher performance at Al-Ittihadiyah Integrated Junior High School Ciampea Udik Bogor. Then it can be concluded that H0 was accepted and Ha was rejected.